Die Register Innocenz´ III 3. Band, erster Teil: 3. Pontifi katsjahr, 1200/1201, das erhaltene Registerfragment, Text und Indices - Maleczek, Werner (Verlag der Österreichischen Akademie der Wissenschaften, 2023)
Edition of the 57 preserved letters from the third year of the registers of pope Innozent III.